2009
DOI: 10.1002/anie.200902963
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐Associated MUC1 Tandem‐Repeat Glycopeptide Microarrays to Evaluate Serum– and Monoclonal–Antibody Specificity

Abstract: The membrane-bound mucin glycoprotein MUC1 is extensively overexpressed on epithelial tumor cells and considered an attractive target in the development of cancer immunotherapy and immunodiagnostics. In epithelial tumors downregulation of glycosyltransferases, in particular the core 2 b-1,6-N-acetylglucosaminyltransferase, and up-regulation of sialyltransferases results in the formation of short saccharides with premature sialylation of the extracellular domain of mucins, [1][2][3][4] exposure of the peptide b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 36 publications
1
38
0
3
Order By: Relevance
“…The resulting BSA-glycoconjugate was injected into rabbits to raise polyclonal antibodies targeting the Arg Rha moiety. 39,40 After the third immunization, the crude anti -sera were collected and their specificity was monitored by employing an enzyme-linked immunosorbent assay (ELISA) analysis with horseradish peroxidase linked anti -rabbit IgG. The antibodies from two batches of crude anti -sera from two immunized rabbits were found to bind robustly and specifically to the BSA-glycoconjugate with high titers, showing strong immune reactivity even after 128 000 fold dilution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting BSA-glycoconjugate was injected into rabbits to raise polyclonal antibodies targeting the Arg Rha moiety. 39,40 After the third immunization, the crude anti -sera were collected and their specificity was monitored by employing an enzyme-linked immunosorbent assay (ELISA) analysis with horseradish peroxidase linked anti -rabbit IgG. The antibodies from two batches of crude anti -sera from two immunized rabbits were found to bind robustly and specifically to the BSA-glycoconjugate with high titers, showing strong immune reactivity even after 128 000 fold dilution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Binding studies with MUC1 glycopeptides bound to microchips [10] showed that the recognition profile of the antibodies induced by the aforementioned vaccines is different from that found for the biologically optimized, tumorselective antibody SM3 [11] . It also differs from those of autoantibodies isolated from serum of tumor patients.…”
Section: Dedicated To Professor Dieter Hoppe On the Occasion Of His 7mentioning
confidence: 86%
“…The MUC1 tetanus toxoid vaccines [9] described above carried the T antigen or the sialyl-T N antigen side chains at threonine-6 of 1, whereas the SM3 antibody [10,11] as well as the autoantibodies in the sera of patients [12] showed intensive binding to MUC1 glycopeptides glycosylated in the GSTA region (Ser 17 , Thr 18 ). NMR spectroscopic analyses had shown that glycan side chains in the STAPPA peptide sequence of MUC1 influence the conformation of this peptide segment.…”
Section: Dedicated To Professor Dieter Hoppe On the Occasion Of His 7mentioning
confidence: 99%
See 1 more Smart Citation
“…They observe high IgG titers to unique glycoforms of MUC1 glycopeptides in various cancers that are completely absent in healthy individuals (150). Westerlind and colleagues have also generated a MUC1 glycopeptide array for similar studies (151). These initial results suggest that this technology will become an important tool for unraveling the “glycopeptidome”.…”
Section: Decoding the Glycome: Biological Applications Of Glycan Micrmentioning
confidence: 99%